Weltagrarbericht: Synthesebericht - Albrecht, Stephan; Engel, Albert (Hamburg University Press, 2009)
The International Assessment of Agricultural Knowledge, Science and Technology for Development[IAASTD] adopted in Johannesburg, South Africa in 2008, is the result of a unique cooperative effort by UN and other international organizations, 60 governments and more than 400 scientists from all over the world.A Global Report and five Regional Reports describe the main problems facing agriculture, food, the environment and human health today and show how the urgent need for a turnaround towards sustainable, environmentally and socially equitable development and food security for a growing world population can be achieved in practice. The synthesis report now published in German summarizes the central analyses and options.